Association between high deductible health plan coverage and age at pediatric umbilical hernia repair - Morgan E Doty; Lindsay A Gil; Jennifer N Cooper (BMJ Publishing Group, 2023)
Background High deductible health plans (HDHPs) are associated with the avoidance of both necessary and unnecessary healthcare. Umbilical hernia repair (UHR) is a procedure that is frequently unnecessarily performed in young children, contrary to best practice guidelines. We hypothesized that children with HDHPs, as compared with other types of commercial health plans, are less likely to undergo UHR before 4 years of age but are also more likely to have UHR delayed beyond 5 years of age.Methods Children aged 0-18 years old residing in metropolitan statistical areas (MSAs) who underwent UHR in 2012-2019 were identified in the IBM Marketscan Commercial Claims and Encounters Database. A quasi-experimental study design using MSA/year-level HDHP prevalence among children as an instrumental variable was employed to account for selection bias in HDHP enrollment. Two-stage least squares regression modeling was used to evaluate the association between HDHP coverage and age at UHR.Results A total of 8601 children were included (median age 5 years, IQR 3-7). Univariable analysis revealed no differences between the HDHP and non-HDHP groups in the likelihood of UHR being performed before 4 years of age (27.7% vs 28.7%, p=0.37) or after 5 years of age (39.8% vs 38.9%, p=0.52). Geographical region, metropolitan area size, and year were associated with HDHP enrollment. Instrumental variable analysis demonstrated no association between HDHP coverage and undergoing UHR at <4 years of age (p=0.76) or >5 years of age (p=0.87).Conclusions HDHP coverage is not associated with age at pediatric UHR. Future studies should investigate other means by which UHRs in young children can be avoided.